Reliability of hemodynamic parameters measured by bioimpedance cardiography at different intensities during incremental exercise testing - Schoch, Raphael; Wagner, Jonathan; Niemeyer, Max; Bruggisser, Fabienne; Infanger, Denis; Carrard, Justin; Gasser, Benedikt; Schmidt-Trucksäss, Arno; Knaier, Raphael (Frontiers in Cardiovascular Medicine, 2025)
BackgroundBioimpedance cardiography offers a non-invasive and time-efficient method to measure hemodynamic parameters. Previous studies only investigated its reliability under steady-state conditions and at maximum load but not at ventilatory thresholds (VTs). This is the first study that assesses the reliability of measured hemodynamic parameters at different exercise stages during cardiopulmonary exercise testing (CPET) using prespecified strict criteria to assess reliability.MethodsData from 31 healthy, well-trained adults were analyzed. Each participant completed two CPETs, both following the same ramp protocol, with a 7-day interval between them. Hemodynamic parameters were measured with the PhysioFlow® (Manatec Biomedical, Poissy, France) at characteristic phases and thresholds [VT1, VT2, and peak oxygen uptake (V̇O2peak)]. To ensure comparability, the wattage (power) corresponding to the thresholds in Test 1 (PVT1, PVT2, and PV̇O2peak) was used for Test 2.ResultsHeart rate, stroke volume, and cardiac output demonstrated good reliability on a group level (mean intraclass correlation >0.75) at both thresholds (0.91, 0.80, and 0.77 at PVT1; 0.92, 0.80, and 0.77 at PVT2) and at PV̇O2peak (0.93, 0.82, and 0.80). For stroke volume at PV̇O2peak, both individual differences (−39.0 to 36.9 mL for the women and −39.9 to 45.2 mL for the men) and mean detectable change (17.5 mL) were larger than the a priori defined acceptable ranges of agreement (−3.6 to 3.8 mL for the women and −4.5 to 3.3 mL for the men).ConclusionThe PhysioFlow® reliably measures heart rate, stroke volume, and cardiac output during CPET on a group level. However, as shown by the Bland–Altman plots, the reliability is too low to be used for individual comparisons.